THE POTENTIAL OF RENEWABLE ENERGY SOURCES IN LATVIA - Sakipova, S.; Jakovics, A.; Gendelis, S. (LATVIAN JOURNAL OF PHYSICS AND TECHNICAL SCIENCES, 2016)
The article discusses some aspects of the use of renewable energy sources in the climatic conditions prevailing in most of the territory of Latvia, with relatively low wind speeds and a small number of sunny days a year. The paper gives a brief description of the measurement equipment and technology to determine the parameters of the outer air; the results of the measurements are also analysed. On the basis of the data obtained during the last two years at the meteorological station at the Botanical Garden of the University of Latvia, the energy potential of solar radiation and wind was estimated. The values of the possible and the actual amount of produced energy were determined.
Keywords: Betz-Zhukovsky criterion; intensity of solar radiation; potential; renewable energy resources; wind speed